The Battle for Italy - Jackson, W. G. F., 1917- (Lahore National Books Foundation, 1972)
The Italian Campaign of World War II was arguably the key to the end of the war in Europe. I\mainland and the campaign on Italian soil until the surrender of the German Armed Forces in Italy in May 1945. It is estimated that between September 1943 and April 1945, some 60,000-70,000 Allied and 60,000-150,000 German soldiers died in Italy .
Include Maps, Appendix and Index
Keywords: World War, 1939-1945 -- Campaigns -- Italy -- Italy -- World War (1939-1945) -- Military Campaigns